Making Lake Erie Smart by Driving Innovations in Technology and Networking - Pearson, Becky; Kearns, Tim; Slawecki, Tad; Stubbs, Bryan; Herzog, Max; Paige, Kelli; Fitch, David (Frontiers in Marine Science, 2019)
Tomorrow’s smart lakes and oceans will be able to, among other things, predict changes in the water environment and produce information critical to proper management and planning. Smart Lake Erie – a proof of concept – will integrate data from distributed sensors using resilient networks to feed adaptive, predictive analytics that define and perhaps even perform necessary management actions. This paper presents the Smart Lake Erie pilot as a series of steps that include convening innovation competitions, engaging stakeholders, securing the core observation system, and designing then building a sustainable early warning system for harmful algal blooms. The pilot’s data platform will show what is needed to serve new data contributors, service providers, stakeholders and consumers of the data and information service paradigm. Lessons learned from the early implementation of the pilot will be applicable to the overall Great Lakes region, other regional associations within the U.S. Integrated Ocean Observing System (IOOS), and the Global Ocean Observing System (GOOS).